Student Community Services In Batik Education For The Young Generation - Sulaiman, Adhi Iman; Sugito, Toto; Prastyanti, Shinta; Windiasih, Rili; Prasetiyo, Prasetiyo (CV. Inara, 2022)
Batik is a heritage of art, culture, economy, and local wisdom products that are unique, and attractive. It has been globally. Central Java has several batik centers, one of which is Batik Gumelem in The sub-District of Susukan, Banjarnegara Regency is a research location. The study aims to construct student community services in batik education for the young generation the art, culture, and products as local wisdom. This study used quantitative methods and descriptive analysis through the distribution of questionnaires with a quota sample of 100 students from high schools and vocational schools at the research location. The result shows that community service as education can be analyzed into three aspects. First, declarative knowledge refers to the student's understanding of the types of batik and the importance of batik lessons to preserve local wisdom products. The second aspect is procedural knowledge which emphasizes the student's interest and assessment that learning batik, especially designing digitalmotifs, is not difficult. However, in the conceptual aspect, students considered that being a batik craftsman and entrepreneur was not prospective to generate a more promising income such as being an employee. Those results show the empowerment of the younger generation in the field of batik since designing both manually and digitally, to the process of batik to coloring is very important, besides skills in eco-print batik product innovation and its marketing promotion strategies through digital media. The empowerment of batik will contribute to developing the motivation, knowledge.